Monoclonal Antibody Therapies for High Risk Neuroblastoma - Furman WL (Dove Medical Press, 2021)
Wayne L Furman Department of Oncology, St. Jude Children’s Research Hospital, Memphis, TN, USACorrespondence: Wayne L FurmanDepartment of Oncology, St. Jude Children’s Research Hospital, 262 Danny Thomas Place, Memphis, TN, 38105, USATel +1-901-595-2403Fax +1– 901-521-9005Email wayne.furman@stjude.orgAbstract: Monoclonal antibodies (mAbs) are part of the standard of care for the treatment of many adult solid tumors. Until recently none have been approved for use in children with solid tumors. Neuroblastoma (NB) is the most common extracranial solid tumor in children. Those with high-risk disease, despite treatment with very intensive multimodal therapy, still have poor overall survival. Results of treatment with an immunotherapy regimen using a chimeric (human/mouse) mAb against a cell surface disialoganglioside (GD2) have changed the standard of care for these children and resulted in the first approval of a mAb for use in children with solid tumors. This article will review the use of the various anti-GD2 mAbs in children with NB, methods that have been or are being evaluated for enhancing their efficacy, as well as review other promising antigenic targets for the therapeutic use of mAbs in children with NB.Keywords: immunotherapy, neuroblastoma, anti-disialoganglioside, anti-GD2, chimeric, effector cells